The Effect of Financial Literacy Programs on Household Saving Behavior in Urban Indonesia - Wulandari (Generasi Sains Indonesia, 2025)
Financial literacy programs have emerged as critical interventions to enhance household financial capability and promote responsible saving behavior, particularly in urban contexts with diverse socio-economic conditions. This study examines the effect of financial literacy programs on household saving behavior in urban Indonesia, employing a quasi-experimental mixed-methods design. Data were collected from 150 households through pre- and post-program surveys, complemented by in-depth interviews and focus group discussions. Quantitative results show significant increases in household savings across all income groups, with lower-income households exhibiting the highest proportional gains (+60%). Middle- and higher-income households also demonstrated notable improvements, though with smaller relative increases. Qualitative findings reveal that participants gained greater awareness of budgeting, savings options, and financial decision-making, while persistent challenges, such as limited access to formal financial services, constrained the full application of knowledge. The study also finds that both male- and female-headed households benefited from the program, and younger participants showed higher adaptability to new saving practices. Overall, the findings suggest that financial literacy programs effectively enhance household saving behavior, increase financial confidence, and contribute to broader social objectives such as gender equity and family welfare. However, to sustain and maximize these benefits, complementary interventions such as accessible financial services, targeted incentives, and supportive policy frameworks are necessary. These insights provide important implications for policymakers, program designers, and financial institutions aiming to strengthen financial inclusion and household economic resilience in urban Indonesia.